Approximate Cubic Lie Derivations on ρ-Complete Convex Modular Algebras - Hark-Mahn Kim; Hwan-Yong Shin (Journal of Function Spaces)
In this article, we present generalized Hyers–Ulam stability results of a cubic functional equation associated with an approximate cubic Lie derivations on convex modular algebras χρ with Δ2-condition on the convex modular functional ρ.